Effect of Weight Training and Leg Length on the Sickle Kick Speed in Male Students Extracurricular Pencak Silat at Senior High School Bina Jaya Palembang (Journal of Physical Education and Sports, 2019)
This study discusses the effect of weight training and leg length on crescent kick speed. The objectives of this study are (1) to analyze the differences in the effect of rubber tire weight training and the ankle weight on the sickle kick speed, (2) analyzing the difference in effect between the long limbs and short legs to the sickle kick speed, (3) analyze the interaction between tire rubber weight training and the ankle weight and leg length in increasing the sickle kick speed. The method used in this study is an experiment with a 2x2 factorial design. The population in this study were all male extracurricular students of Senior High School Bina Jaya Palembang. Sampling in this study used total sampling technique. From two-way ANOVA testing shows that all three hypotheses are accepted. The first hypothesis reads "there is a difference in the effect of rubber weight training and ankle weight on the sickle kick speed in male students extracurricular Pencak Silat at Senior High School Bina Jaya Palembang "is acceptable, because it has a Sig. = 0.000 < 0.05. The second hypothesis which reads "there is a difference in influence between the length of the limb and the speed of the sickle kick of male students extracurricular Pencak Silat at Senior High School Bina Jaya Palembang" was also accepted, because it has a Sig. = 0.026 < 0.05. The third hypothesis which reads "there is an interaction between tire rubber weight training, ankle weight and leg length in increasing the sickle kick speed in male students extracurricular Pencak Silat at Senior High School Bina Jaya Palembang" is acceptable, because it has a Sig. = 0.032 < 0.05. The results showed a difference in the effect of rubber tire weight training, and leg length on the sickle kick speed and there was an interaction between weight training and leg length in increasing the sickle kick speed.